Ni-Based Electrocatalysts for Unconventional CO2 Reduction Reaction to Formic Acid - Albero, Josep; Lepre, Enrico; Heske, Julian; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo Zizak; Heil, Tobias Heil; D. Kühne, Thomas; Antonietti, Markus; López-Salas, Nieves (Proceedings of the International Conference on Frontiers in Electrocatalytic Transformations)

A fully cross-diffusive two-component evolution system: Existence and qualitative analysis via entropy-consistent thin-film-type approximation. - Tao, Youshan; Winkler, Michael (Journal of Functional Analysis)

The dampening role of large repulsive convection in a chemotaxis system modeling tumor angiogenesis. - Tao, Youshan; Winkler, Michael (Nonlinear Analysis, Theory, Methods and Applications)

Immediate regularization of measure-type population densities in a two-dimensional chemotaxis system with signal consumption. - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Science China Mathematics)

Small-density solutiions in Keller-Segel systems involving rapidly decaying diffusivities. - Ding, Mengyao; Winkler, Michael (Nonlinear Differential Equatiions and Applicatiions)

Global smooth solutions in a two-dimensional cross-diffusion system modeling propagation of urban crime. - Tao, Youshan; Winkler, Michael (Communications in Mathematical Sciences)

Taxis-driven formation of singular hotspots in a May-Nowak type model for virus infection. - Tao, Youshan; Winkler, Michael (SIAM Journal on Mathematical Analysis)

Local energy estimates and global solvability in a threee-dimensional chemotaxis-fluid system with prescribed signal on the boundary. - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Communications in Partial Differential Equations)

Global solvability in a threee-dimensional Keller-Segel.Stokes system involving arbitrary superlinear logistic degradation - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Advances in Nonlinear Analysis)

Critical mass for infinite-time blow-up in a haptotaxis system with nonlinear zero-order interaction - Tao, Youshan; Winkler, Michael (Discrete and Continuous Dynamical Systems)

„Vom Fahr-Zeug zum Fahr-Ding. Ein Heideggerianischer Kommentar zum autonomen Automobil“ - Alpsancar, Suzana (Autonome Autos – Die Zukunft des Verkehrs und die Dispositive der Mobilität)

Building, emptying out, or dreaming? Action structures and space in students’ metaphors of academic writing - Scharlau, Ingrid; Karsten, A.; Rohlfing, Katharina J. (Journal of Writing Research)
Keywords: Literature and Literary Theory; Linguistics and Language; Language and Linguistics; Education

Comparing the Effects of a Different Social Partner (Social Robot vs. Human) on Children's Social Referencing in Interaction - Tolksdorf, Nils Frederik; Crawshaw, Camilla E.; Rohlfing, Katharina J. (Frontiers in Education)
Social robots have emerged as a new digital technology that is increasingly being implemented in the educational landscape. While social robots could be deployed to assist young children with their learning in a variety of different ways, the typical approach in educational practices is to supplement the learning process rather than to replace the human caregiver, e.g., the teacher, parent, educator or therapist. When functioning in the role of an educational assistant, social robots will likely constitute a part of a triadic interaction with the child and the human caregiver. Surprisingly, there is little research that systematically investigates the role of the caregiver by examining the ways in which children involve or check in with them during their interaction with another partner — a phenomenon that is known as social referencing. In the present study, we investigated social referencing in the context of a dyadic child–robot interaction. Over the course of four sessions within our longitudinal language-learning study, we observed how 20 pre-school children aged 4–5 years checked in with their accompanying caregivers who were not actively involved in the language-learning procedure. The children participating in the study were randomly assigned to either an interaction with a social robot or a human partner. Our results revealed that all children across both conditions utilized social referencing behaviors to address their caregiver. However, we found that the children who interacted with the social robot did so significantly more frequently in each of the four sessions than those who interacted with the human partner. Further analyses showed that no significant change in their behavior over the course of the sessions could be observed. Findings are discussed with regard to the caregiver's role during children's interactions with social robots and the implications for future interaction design.

Do Shy Children Keep more Distance from a Social Robot? Exploring Shy Children’s Proxemics with a Social Robot or a Human - Tolksdorf, Nils Frederik; Viertel, Fanziska E.; Crawshaw, Camilla E.; Rohlfing, Katharina J. (Interaction Design and Children)

Nonlinear waveguides for integrated quantum light source - Domeneguetti, Renato R.; Conradi, Hauke; Kleinert, Moritz; Kießler, Christian; Stefszky, Michael; Herrmann, Harald; Silberhorn, Christine; Andersen, Ulrik L.; Neergaard-Nielsen, Jonas Schou; Gehring, Tobias (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference)
We experimentally investigate the generation of continuous-wave optical squeezing from a titanium-indiffused lithium niobate waveguide resonator at low and high frequencies. The device promises integration with different platform chips for more complex optical systems.
Keywords: Optical systems; Polymer waveguides; Quantum key distribution; Quantum light sources; Squeezed states; Waveguides

Lehrerkooperation und Digitalisierung - Gestaltung digital-kooperativer Arbeitsbeziehungen von Lehrkräften und ReferendarInnen am Beispiel des Schulfachs Pädagogik - Engemann, M.; Herzig, Bardo (Fachliche Bildung und digitale Transformation - Fachdidaktische Forschung und Diskurse. Fachtagung der Gesellschaft für Fachdidaktik 2020)

Prospektive und prozessbezogene Kompetenzanalyse - Gestaltung und Erprobung eines Vorgehens - Depenbusch, Sarah; Bender, Elena; Schaper, Niclas

Investigating the multidimensionality of informal learning: Validation of a short measure for white‐collar workers - Decius, Julian; Knappstein, Michael; Schaper, Niclas; Seifert, Andreas (Human Resource Development Quarterly)
Keywords: Organizational Behavior and Human Resource Management; Arts and Humanities (miscellaneous)

The Hen-Egg-Problem of Informal Workplace Learning & Work Design: The Mediating Role of Job Crafting. - Decius, Julian; Schaper, Niclas; Seifert, Andreas (Academy of Management Prodeedings)

Seismograf Pop - Jacke, Christoph; Roenneke, Stefanie; Göymen, Cigdem (Pop-Musik*)

Multimode integrated SU(1,1) interferometer - Ferreri, A.; Santandrea, Matteo; Stefszky, Michael; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine; Sharapova, Polina (Conference on Lasers and Electro-Optics)
We present a frequency multimode integrated SU (1,1) interferometer with a polarization converter and strong signal-idler photon correlations. Phase sensitivity below the shot noise limit is demonstrated, various filtering and seeding strategies are discussed.

Sachunterricht lehren in Zeiten der Pandemie – Eine Online-Befragung zu den Auswirkungen der digitalen Lehre auf den Materialeinsatz und die Selbstwirksamkeitserwartungen von Lehrenden in der Sachunterrichtsdidaktik an drei deutschen Hochschulstandorten. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Thonemann, Lisa; Reh, Anne; Deutschen, Katrin; Lakemeyer, Jana Marie; Blumberg, Eva

Digitales Sachunterrichtsstudium in der Corona-Krise – Eine empirische Evaluationsstudie zur Rezeption des analogen und webbasierten Unterstützungsangebots des Paderborner Lernzentrums „Sachunterrichtstreff“ bei Sachunterrichtsstudierenden im Grund- und Förderschullehramt. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Deppe, Franziska; Reh, Anne; Blumberg, Eva

Voraussetzungen bei Sachunterrichtsstudierenden zum Herausforderungsbereich Digitalisierung in Schule und Hochschule – Eine empirische Online-Befragung bei Lehramtsstudierenden an Grundschulen und für sonderpädagogische Förderung. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Brenke, Laurien; Blumberg, Eva

Einsatz digitaler Medien im Sachunterricht – Die Coronakrise als Spiegel für die fehlende Digitalisierung im deutschen Bildungswesen? Was können wir von Schweden lernen? Vortrag auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Sicking, Annika; Blumberg, Eva

Digital gestütztes Lernen im naturwissenschaftlichen Sachunterricht? Eine kriteriengeleitete Analyse digitaler sachunterrichtsbezogener Lernangebote. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Stump, Martin; Blumberg, Eva

Prozessmodell Generative Unterrichtsplanung Sachunterricht (GUS). Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Tänzer, Sandra; Lauterbach, Roland; Blumberg, Eva; Grittner, Frauke; Lange, Jochen; Schomaker, Claudia

transMINT4.0 – Grenzen überwinden, MINT-Bildung verbinden durch außerschulische Lernorte und den Einsatz digitaler Medien. Eingeladener digital synchroner Vortrag in der MINT-Aktionswoche von MINTvernetzt - Blumberg, Eva; Schulze, Jan Roland; Temmen, Katrin; Schäfers, Johannes

Preisabsprachen in der Automobilindustrie - eine wettbewerbspolitische Analyse - Yigitbas , Osman

Facebooks digitale Währung - eine wettbewerbspolitische Analyse - Schulte, Marcel

Faszination 3D-Film: Entwicklung einer 3D-Konstruktion - Hüsing, Sven; Weiser, Niklas; Biehler, Rolf (mathematik lehren)

Der Beruf Grundschullehrer*in: Zukunftsfragen. Podcast im Rahmen der Reihe „Zukunftsgespräche“ der Peter Gläsel Stiftung - Büker, Petra
März 2021 https://pg-stiftung.net/zukunftsgespraeche/

Children as (Co)Researchers as an Opportunity to influence School Life: A Didactic Approach and its Relevance in the Perspective of Children. Beitrag im Rahmen des Symposiums: Participation to Connect Members of the School Community an der ECER (European Conference on Educational Research), University of Geneva. Online - Büker, Petra; Hüpping, Birgit
September 2021

Partizipation als Veränderung. Eine Aufforderung an Grundschule und Forschung - Büker, Petra; Hüpping, Birgit; Zala-Mezö, Enikö (Zeitschrift für Grundschulforschung)

Simulation of Guided Waves in Cylinders Subject to Arbitrary Boundary Conditions Using the Scaled Boundary Finite Element Method - Itner, D.; Gravenkamp, H.; Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd (14th WCCM-ECCOMAS Congress)

CxNy: New Carbon Nitride Organic Photocatalysts - Lopez Salas, Nieves; Albero, Josep (Frontiers in Materials)
The search for metal-free and visible light-responsive materials for photocatalytic applications has attracted the interest of not only academics but also the industry in the last decades. Since graphitic carbon nitride (g-C 3 N 4 ) was first reported as a metal-free photocatalyst, this has been widely investigated in different light-driven reactions. However, the high recombination rate, low electrical conductivity, and lack of photoresponse in most of the visible range have elicited the search for alternatives. In this regard, a broad family of carbon nitride (C x N y ) materials was anticipated several decades ago. However, the attention of the researchers in these materials has just been awakened in the last years due to the recent success in the syntheses of some of these materials (i.e., C 3 N 3 , C 2 N, C 3 N, and C 3 N 5 , among others), together with theoretical simulations pointing at the excellent physico-chemical properties (i.e., crystalline structure and chemical morphology, electronic configuration and semiconducting nature, or high refractive index and hardness, among others) and optoelectronic applications of these materials. The performance of C x N y , beyond C 3 N 4 , has been barely evaluated in real applications, including energy conversion, storage, and adsorption technologies, and further work must be carried out, especially experimentally, in order to confirm the high expectations raised by simulations and theoretical calculations. Herein, we have summarized the scarce literature related to recent results reporting the synthetic routes, structures, and performance of these materials as photocatalysts. Moreover, the challenges and perspectives at the forefront of this field using C x N y materials are disclosed. We aim to stimulate the research of this new generation of C x N y -based photocatalysts, beyond C 3 N 4 , with improved photocatalytic efficiencies by harnessing the striking structural, electronic, and optical properties of this new family of materials.
Keywords: Materials Science (miscellaneous)

CuII/CuI decorated N-doped carbonaceous electrocatalysts for the oxygen reduction reaction - Kossmann, Janina; Ortíz Sánchez-Manjavacas, María Luz; Zschiesche, Hannes; Tarakina, Nadezda V.; Antonietti, Markus; Albero, Josep; Lopez Salas, Nieves (Journal of Materials Chemistry A)
Copper- and nitrogen-doped carbonaceous materials, obtained by a simple synthetic procedure are highly efficient and fast catalysts for the oxygen reduction reaction. It is shown, that Cu( i ) containing materials perform with faster reaction kinetics.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Ultrahigh water sorption on highly nitrogen doped carbonaceous materials derived from uric acid - Kossmann, Janina; Rothe, Regina; Heil, Tobias; Antonietti, Markus; Lopez Salas, Nieves (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

An interrater reliability study of gait analysis systems with the dual task paradigm in healthy young and older adults - Klotzbier, Thomas Jürgen; Wollesen, Bettina; Vogel, Oliver; Rudisch, Julian; Cordes, Thomas; Jöllenbeck, Thomas; Vogt, Lutz (European Review of Aging and Physical Activity)
Abstract Background and aims One reason for the controversial discussion of whether the dual task (DT) walking paradigm has an added value for diagnosis in clinical conditions might be the use of different gait measurement systems. Therefore, the purpose was 1) to detect DT effects of central gait parameters obtained from five different gait analysis devices in young and old adults, 2) to assess the consistency of the measurement systems, and 3) to determine if the absolut and proportional DT costs (DTC) are greater than the system-measurement error under ST. Methods Twelve old (72.2 ± 7.9y) and 14 young adults (28.3 ± 6.2y) walked a 14.7-m distance under ST and DT at a self-selected gait velocity. Interrater reliability, precision of the measurement and sensitivity to change were calculated under ST and DT. Results An age effect was observed in almost all gait parameters for the ST condition. For DT only differences for stride length ( p < .029, ɳ 2 p = .239) as well as single and double limb support ( p = .036, ɳ 2 p = .227; p = .034, ɳ 2 p = .218) remained. The measurement systems showed a lower absolute agreement compared to consistency across all systems. Conclusions When reporting DT effects, the real changes in performance and random measurement errors should always be accounted for. These findings have strong implications for interpreting DT effects.
Keywords: Geriatrics and Gerontology

Agreement and consistency of five different clinical gait analysis systems in the assessment of spatiotemporal gait parameters - Rudisch, Julian; Jöllenbeck, Thomas; Vogt, Lutz; Cordes, Thomas; Klotzbier, Thomas Jürgen; Vogel, Oliver; Wollesen, Bettina (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

Chancen des inklusionsorientierten Sachunterrichts für didaktisch-diagnostisches Handeln. Konzeptionelle und methodologisch-methodische Grundlagen eines forschungsbasierten Entwicklungsansatzes für die Lehrer*innenbildung - Schroeder, René; Blumberg, Eva; Kottmann, Brigitte; Miller, Susanne; Reh, Anne (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
In der Herausforderung Unterricht inklusionsbezogen weiterzuentwickeln, manifestiert sich unter anderem die Forderung nach der Qualifizierung von (angehenden) Lehrkräften bzgl. der Anwendung und Umsetzung einer alltagsintegrierten Diagnostik mit dem Ziel, Kinder individualisiert und gleichzeitig mit Bezug auf einen gemeinsamen Lerngegenstand zu unterrichten. Dabei ist ein didaktisch-diagnostisches Handeln aller Lehrkräfte gefordert, welches im Kontext einer professionellen und inklusionsorientierten Gestaltung sowie einer angemessenen Begleitung und Förderung von Lern- und Entwicklungsprozessen steht. In der Konzeption entsprechender Aus- und Weiterbildungsformate setzt das geplante Projekt DiPoSa (Didaktisch-diagnostische Potentiale des inklusionsorientierten Sachunterrichts) an. Ziel ist es durch einen Design-Based-Research-Ansatz (DBR) Videovignetten zu erstellen und zu evaluieren, mittels derer entsprechende Kompetenzen von (angehenden) Lehrkräften im Sachunterricht weiterentwickelt werden können. Dabei bietet insbesondere der Sachunterricht als vielperspektivisches Integrationsfach der Grundschule einen passenden Rahmen, kindliche Lernpotentiale als Ausgangspunkt für didaktisch-diagnostisches Handeln nutzbar zu machen. Denn in aktuellen inklusionsorientierten Ansätzen des Sachunterrichts sind sowohl reformpädagogisch orientierte als auch offene Konzepte und Modelle des adaptiven Unterrichts zu finden, die sich an den unterschiedlichen Programmatiken der Umsetzung von individueller Förderung orientieren. Im folgenden Beitrag werden die dem geplanten Projekt zugrundeliegenden theoretischen und empirischen Zugänge erläutert und die forschungsmethodische Umsetzung durch einen DBR-Ansatz als methodologische Basis für eine Theorie-Praxis-verzahnende Forschungsperspektive auf diagnostisches Handeln sowie die Förderung diagnostischer Handlungskompetenzen durch Videovignetten im Kontext der Aus- und Weiterbildung von (Sachunterrichts-)Lehrkräften diskutiert. Abstract The challenge to further promote practices of inclusive teaching, requires the development of assessment literacy. Combined with the aim to teach all children in a collaborative learning environment, qualification of teachers (in training) in the application and implementation of formative assessment as an integrated daily routine is needed. Therefore, the project DiPoSa focuses on the development of appropriate training and qualification formats. The project heads to create and evaluate video vignettes using a design-based-research approach (DBR), which can then be used to further develop assessment literacy of teachers in social studies and science in primary education. As a multi-perspective integrative subject in elementary school social studies and science in primary education offers a suitable framework for practices of formative assessment taking children's learning potentials as a serious concern. Foundations can be seen in current inclusive approaches to social studies and science in primary education, where reform pedagogically orientation and open concepts can as well be found as models of adaptive teaching. Although there are different theoretical and programmatic implementations, both perspectives share an orientation towards individual support of children. With this in mind the following article tries to lay down the theoretical and empirical approaches of the planed project DiPoSa and discusses methodological foundations of the project. The discussion focuses on how assessment practices as well as assessment literacy can be promoted through a DBR research-design using video vignettes in the context of teacher education and qualification and rooting in a deepened science-practice partnership.Zusammenfassung englisch

Berufsspezifische Reflexionsprozesse durch Einzelfallarbeit im Projekt „Schule für alle": Analyse von zwei Praxisberichten mittels der Dokumentarischen Methode - Reh, Anne; Kottmann, Brigitte; Miller, Susanne (QfI - Qualifizierung für Inklusion)
In dem Beitrag wird ausgehend von der Notwendigkeit einer inklusionspädagogischen Professionalisierung im Lehramtsstudium ein erziehungswissenschaftliches Projekt dargestellt, das es den teilnehmenden Bachelor-Studierenden in besonderer Weise ermöglicht, berufsspezifische Reflexionsprozesse zu durchlaufen. In dem Projekt übernehmen Studierende die einjährige pädagogische Förderung von Grundschulkindern mit bildungsrelevanten Benachteiligungsfaktoren, die häufig von Selektionspraktiken und -maßnahmen bedroht sind. Die Bearbeitung von vorliegenden Common-Sense-Theorien im inklusiven Kontext gilt dabei als ein relevantes Professionalisierungsziel in der Lehramtsausbildung. Konkret werden Ausschnitte aus Praktikumsberichten von zwei Studierenden mittels der dokumentarischen Methode ausgewertet und einander gegenübergestellt, um daran herauszuarbeiten, inwiefern sich die Reflexionen unterscheiden. Es zeigt sich anhand der Analysen, dass im Rahmen der Praxisphase eine Reflection-on-Action und auch die vertiefte Reflexion eigener Common-Sense-Theorien grundsätzlich möglich, jedoch nicht voraussetzungslos ist. Insbesondere kann auch anhand der gewählten Einzelfälle verdeutlicht werden, wie individuell inklusionsbezogene Professionalisierungsprozesse im Rahmen der vorliegenden Praxisphase verlaufen können. Die Analyse offenbart multiple Professionalisierungschancen in Abhängigkeit von den Rahmenbedingungen des Projekts, den individuellen Schwerpunkten der pädagogischen Arbeit oder den individuellen Reflexionen der Studierenden. Abstract Based on the necessity of an inclusive pedagogical professionalisation in the teacher training program, this article presents an educational science project that enables the participating Bachelor students in a unique manner to go through profession-specific reflection processes. In the project, students take on the one-year pedagogical support of primary school children with educational disadvantage factors, who are often threatened by selection practices and measures. In this context, working through present common-sense theories in an inclusive context is considered a relevant professionalization goal in teacher education. Specifically, excerpts from internship reports of two students are analysed by means of the documentary method and compared to each other in order to work out the extent to which the reflections differ. The analyses show that reflection-on-action and in-depth reflection on one's own common-sense theories are generally possible during the practical phase, but not without preconditions. In particular, the selected individual cases can be used to illustrate how individual inclusion-related professionalisation processes can take place within the framework of the present practical phase. The analysis reveals multiple opportunities for professionalisation depending on the general framework of the project, the individual focal points of the pedagogical work or the individual reflections of the students.

Übergänge begleiten. Peer-Beratung beim Übergang für Lernende mit Förderbedarf - Kottmann, Brigitte (Schule inklusiv - Vielfalt nutzen - Bildungsgerechtigkeit schaffen)

Rezension des Buches: "Sonderschule im Nationalsozialismus. Die Magdeburger Hilfsschule als Modell von Dagmar Hänsel (2019) - Kottmann, Brigitte (Zeitschrift für Heilpädagogik)

Towards a Trust-Aware Item Recommendation System on a Graph Autoencoder with Attention Mechanism - Meydani, Elnaz; Düsing, Christoph; Trier, Matthias (Lecture Notes in Information Systems and Organisation)

The potential and global outlook of integrated photonics for quantum technologies - Pelucchi, Emanuele; Fagas, Giorgos; Aharonovich, Igor; Englund, Dirk; Figueroa, Eden; Gong, Qihuang; Hannes, Hübel; Liu, Jin; Lu, Chao-Yang; Matsuda, Nobuyuki; Pan, Jian-Wei; Schreck, Florian; et al. (Nature Reviews Physics)
Keywords: General Physics and Astronomy

Distributed Algorithms for Spectral and Energy-Efficiency Maximization of $K$-User Interference Channels - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J (IEEE Access)

Rate Region of the $K$-user MIMO Interference Channel with Imperfect Transmitters - Soleymani, Mohammad; Santamaria, Ignacio; Maham, Behrouz; Schreier, Peter J (Proc. 28th European Signal Processing Conference (EUSIPCO))

Nihil est sine sono (1. Kor. 14,10). Musik in interkulturellen Begegnungen. Reinhold Bernhardt / Verena Grüter (Hg.): Musik in interreligiösen Begegnungen, TVZ Zürich 2019, 216 S - Schroeter-Wittke, Harald (Praktische Theologie)

4. Sonntag nach Trinitatis (27.6.2021). Gen 50,15-21: Diplomatische Wahrheit oder : Am Ziel der Träume – alles anders - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Das besondere Buch. Ralf Koerrenz und Tobias Nicklas (Hg.): Bildung. Jahrbuch für Biblische Theologie 35, Göttingen 2021 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Probing the Interactions of Immobilized Ruthenium Dihydride Complexes with Metal Oxide Surfaces by MAS NMR: Effects on CO2 Hydrogenation - Nguyen, Hoang-Huy; Li, Zheng; Enenkel, Toni; Hildebrand, Joachim; Bauer, Matthias; Dyballa, Michael; Estes, Deven P. (The Journal of Physical Chemistry C)
Homogeneous catalysts immobilized on metal oxides often have different catalytic properties than in homogeneous solution. This can be either activating or deactivating and is often attributed to interactions of catalyst species with the metal oxide surface. However, few studies have ever demonstrated the effect that close associations of active sites with surfaces have on the catalytic activity. In this paper, we immobilize H2Ru(PPh3)2(Ph2P)2N–C3H6–Si(OEt)3 (3) on SiO2, Al2O3, and ZnO and interrogate the relationship to the surface using IR, MAS NMR, 1H–31P HETCOR, and XAS spectroscopies. We found that while there are close contacts between the P atoms of the complex and all three metal oxide surfaces, the Ru–H bond only reacts with oxygen bridges on SiO2 and Al2O3, forming new Ru–O bonds. In contrast, complex 3 stays intact on ZnO. Comparison of the catalytic activities of our immobilized species for CO2 hydrogenation to ethyl formate showed that Lewis acidic metal oxides activate, rather than deactivate, complex 3 in the order Al2O3 > ZnO > SiO2. The Lewis acidic sites on the metal oxide surfaces most likely increase the productivity by increasing the rate of esterification of formate intermediates.
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Olefin Metathesis in Confinement: Towards Covalent Organic Framework Scaffolds for Increased Macrocyclization Selectivity - Emmerling, Sebastian T.; Ziegler, Felix; Fischer, Felix R.; Schoch, Roland; Bauer, Matthias; Plietker, Bernd; Buchmeiser, Michael R.; Lotsch, Bettina V. (Chemistry – A European Journal)
Covalent organic frameworks (COFs) offer vast structural and chemical diversity enabling a wide and growing range of applications. While COFs are well-established as heterogeneous catalysts, so far, their high and ordered porosity has scarcely been utilized to its full potential when it comes to spatially confined reactions in COF pores to alter the outcome of reactions. Here, we present a highly porous and crystalline, large-pore COF as catalytic support in α,ω-diene ring-closing metathesis reactions, leading to increased macrocyclization selectivity. COF pore-wall modification by immobilization of a Grubbs-Hoveyda-type catalyst via a mild silylation reaction provides a molecularly precise heterogeneous olefin metathesis catalyst. An increased macro(mono)cyclization (MMC) selectivity over oligomerization (O) for the heterogeneous COF-catalyst (MMC:O=1.35) of up to 51 % compared to the homogeneous catalyst (MMC:O=0.90) was observed along with a substrate-size dependency in selectivity, pointing to diffusion limitations induced by the pore confinement.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Higher MLCT lifetime of carbene iron(ii) complexes by chelate ring expansion - Reuter, Thomas; Kruse, Ayla; Schoch, Roland; Lochbrunner, Stefan; Bauer, Matthias; Heinze, Katja (Chemical Communications)
Combining strong σ-donating N-heterocyclic carbene ligands and π-accepting pyridine ligands with a high octahedricity in rigid iron(II) complexes increases the 3MLCT lifetime from 0.15 ps in the prototypical [Fe(tpy)2]2+ complex to 9.2 ps in [Fe(dpmi)2]2+12+. The tripodal CNN ligand dpmi (di(pyridine-2-yl)(3-methylimidazol-2-yl)methane) forms six-membered chelate rings with the iron(II) centre leading to close to 90° bite angles and enhanced iron-ligand orbital overlap
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Photoactive iron complexes: more sustainable, but still a challenge - Dierks, Philipp; Vukadinovic, Yannik; Bauer, Matthias (Inorganic Chemistry Frontiers)
On transition metals such as iron rests lots of hope to replace precious metal catalysts in the field of photochemistry for a more sustainable future. Indeed, significant progress has been made in recent years in terms of lifetime extension and emerging applications in catalysis. For this reason, recent synthetic strategies of new photoactive iron compounds, which have proved to show particularly promising properties, are reviewed here. The lifetime of the excited state serves as a key parameter for comparison with the standard ruthenium complex, [Ru(bpy)3]2+, to discuss the potential and performance of the iron complexes. This approach is complemented by a more holistic examination of the sustainability of such a substitution strategy in order to answer the question: when or at which point can we assume that iron represents a more sustainable alternative for noble metals in photochemical applications?
Keywords: Inorganic Chemistry

Selective Benzylic CH‐Borylations by Tandem Cobalt Catalysis - Ghosh, Pradip; Schoch, Roland; Bauer, Matthias; Jacobi von Wangelin, Axel (Angewandte Chemie International Edition)
Metal-catalyzed C−H activations are environmentally and economically attractive synthetic strategies for the construction of functional molecules as they obviate the need for pre-functionalized substrates and minimize waste generation. Great challenges reside in the control of selectivities, the utilization of unbiased hydrocarbons, and the operation of atom-economical dehydrocoupling mechanisms. An especially mild borylation of benzylic CH bonds was developed with the ligand-free pre-catalyst Co[N(SiMe3)2]2 and the bench-stable and inexpensive borylation reagent B2pin2 that produces H2 as the only by-product. A full set of kinetic, spectroscopic, and preparative mechanistic studies are indicative of a tandem catalysis mechanism of CH-borylation and dehydrocoupling via molecular CoI catalysts.
Keywords: General Chemistry; Catalysis

Electrochemical Reduction and Oxidation of Ruddlesden–Popper-Type La2NiO3F2 within Fluoride-Ion Batteries - Wissel, Kerstin; Schoch, Roland; Vogel, Tobias; Donzelli, Manuel; Matveeva, Galina; Kolb, Ute; Bauer, Matthias; Slater, Peter R.; Clemens, Oliver (Chemistry of Materials)
Within this article, it is shown that an electrochemical defluorination and additional fluorination of Ruddlesden–Popper-type La2NiO3F2 is possible within all-solid-state fluoride-ion batteries. Structural changes within the reduced and oxidized phases have been examined by X-ray diffraction studies at different states of charging and discharging. The synthesis of the oxidized phase La2NiO3F2+x proved to be successful by structural analysis using both X-ray powder diffraction and automated electron diffraction tomography techniques. The structural reversibility on re-fluorinating and re-defluorinating is also demonstrated. Moreover, the influence of different sequences of consecutive reduction and oxidation steps on the formed phases has been investigated. The observed structural changes have been compared to changes in phases obtained via other topochemical modification approaches such as hydride-based reduction and oxidative fluorination using F2 gas, highlighting the potential of such electrochemical reactions as alternative synthesis routes. Furthermore, the electrochemical routes represent safe and controllable synthesis approaches for novel phases, which cannot be synthesized via other topochemical methods. Additionally, side reactions, occurring alongside the desired electrochemical reactions, have been addressed and the cycling performance has been studied.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

η 3 ‐Coordination and Functionalization of the 2‐Phosphaethynthiolate Anion at Lanthanum(III)** - Watt, Fabian A.; Burkhardt, Lukas; Schoch, Roland; Mitzinger, Stefan; Bauer, Matthias; Weigend, Florian; Goicoechea, Jose M.; Tambornino, Frank; Hohloch, Stephan (Angewandte Chemie International Edition)
We present the η3-coordination of the 2-phosphaethynthiolate anion in the complex (PN)2La(SCP) (2) [PN=N-(2-(diisopropylphosphanyl)-4-methylphenyl)-2,4,6-trimethylanilide)]. Structural comparison with dinuclear thiocyanate-bridged (PN)2La(μ-1,3-SCN)2La(PN)2 (3) and azide-bridged (PN)2La(μ-1,3-N3)2La(PN)2 (4) complexes indicates that the [SCP]− coordination mode is mainly governed by electronic, rather than steric factors. Quantum mechanical investigations reveal large contributions of the antibonding π*-orbital of the [SCP]− ligand to the LUMO of complex 2, rendering it the ideal precursor for the first functionalization of the [SCP]− anion. Complex 2 was therefore reacted with CAACs which induced a selective rearrangement of the [SCP]− ligand to form the first CAAC stabilized group 15–group 16 fulminate-type complexes (PN)2La{SPC(RCAAC)} (5 a,b, R=Ad, Me). A detailed reaction mechanism for the SCP-to-SPC isomerization is proposed based on DFT calculations.
Keywords: General Chemistry; Catalysis

Electronic Structure of a Diiron Complex: A Multitechnique Experimental Study of [(dppf)Fe(CO) 3]+/0 - Winkler, Mario; Schnierle, Marc; Ehrlich, Felix; Mehnert, Kim-Isabelle; Hunger, David; Sheveleva, Alena M.; Burkhardt, Lukas; Bauer, Matthias; Tuna, Floriana; Ringenberg, Mark R.; van Slageren, Joris (Inorganic Chemistry)
Here we explore the electronic structure of the diiron complex [(dppf)Fe(CO)3]0/+ [10/+; dppf = 1,1′-bis(diphenylphosphino)ferrocene] in two oxidation states by an advanced multitechnique experimental approach. A combination of magnetic circular dichroism, X-ray absorption and emission, high-frequency electron paramagnetic resonance (EPR), and Mössbauer spectroscopies is used to establish that oxidation of 10 occurs on the carbonyl iron ion, resulting in a low-spin iron(I) ion. It is shown that an unequivocal result is obtained by combining several methods. Compound 1+ displays slow spin dynamics, which is used here to study its geometric structure by means of pulsed EPR methods. Surprisingly, these data show an association of the tetrakis[3,5-bis(trifluoromethylphenyl)]borate counterion with 1+.
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Planar Iron Hydride Nanoclusters: Combined Spectroscopic and Theoretical Insights into Structures and Building Principles - Chakraborty, Uttam; Bügel, Patrick; Fritsch, Lorena; Weigend, Florian; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemistryOpen)
The controlled assembly of well-defined planar nanoclusters from molecular precursors is synthetically challenging and often plagued by the predominant formation of 3D-structures and nanoparticles. Herein, we report planar iron hydride nanoclusters from reactions of main group element hydrides with iron(II) bis(hexamethyldisilazide). The structures and properties of isolated Fe4, Fe6, and Fe7 nanoplatelets and calculated intermediates enable an unprecedented insight into the underlying building principle and growth mechanism of iron clusters, metal monolayers, and nanoparticles.
Keywords: General Chemistry

In Krisen erzählen – von Krisen erzählen. Sprachliche, literarische und mediale Dimensionen.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Networks - Sackel, Johanna; Wöbse, Anna-Katharina (A Cultural History of the Sea in the Global Age)

Mehrdeutigkeiten
Keywords: General Earth and Planetary Sciences; General Environmental Science

Register and Instruction Coverage Analysis for Different RISC-V ISA Modules - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Scheytt, Christoph (Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV 2021))

Loyalty programs as travel companions: Complementary service features across customer journey stages - Steinhoff, Lena; Zondag, Marcellis M. (Journal of Business Research)
Keywords: Marketing

 Zeitschrift für Romanische Sprachen und ihre Didaktik

Konstruktionen und Konstruktionslernen

 Zeitschrift für Romanische Sprachen und ihre Didaktik

Phase Noise Investigation for a Radar System with Optical Clock Distribution - Kruse, Stephan; Bahmanian, Meysam; Kneuper, Pascal; Kress, Christian; Kurz, Heiko G.; Schneider, Thomas; Scheytt, Christoph (The 17th European Radar Conference)

Determination of Crystal-Field Splitting Induced by Thermal Oxidation of Titanium - Wojtaszek, Klaudia; Błachucki, Wojciech; Tyrała, Krzysztof; Nowakowski, Michał; Zaja̧c, Marcin; Stȩpień, Joanna; Jagodziński, Paweł; Banaś, Dariusz; Stańczyk, Wiktoria; Czapla-Masztafiak, Joanna; Kwiatek, Wojciech M.; Szlachetko, Jakub; et al. (The Journal of Physical Chemistry A)
Keywords: Physical and Theoretical Chemistry

Comparing the Effects of a Different Social Partner (Social Robot vs. Human) on Children's Social Referencing in Interaction - Tolksdorf, Nils F.; Crawshaw, Camilla E.; Rohlfing, Katharina (Frontiers in Education)
Social robots have emerged as a new digital technology that is increasingly being implemented in the educational landscape. While social robots could be deployed to assist young children with their learning in a variety of different ways, the typical approach in educational practices is to supplement the learning process rather than to replace the human caregiver, e.g., the teacher, parent, educator or therapist. When functioning in the role of an educational assistant, social robots will likely constitute a part of a triadic interaction with the child and the human caregiver. Surprisingly, there is little research that systematically investigates the role of the caregiver by examining the ways in which children involve or check in with them during their interaction with another partner — a phenomenon that is known as social referencing. In the present study, we investigated social referencing in the context of a dyadic child–robot interaction. Over the course of four sessions within our longitudinal language-learning study, we observed how 20 pre-school children aged 4–5 years checked in with their accompanying caregivers who were not actively involved in the language-learning procedure. The children participating in the study were randomly assigned to either an interaction with a social robot or a human partner. Our results revealed that all children across both conditions utilized social referencing behaviors to address their caregiver. However, we found that the children who interacted with the social robot did so significantly more frequently in each of the four sessions than those who interacted with the human partner. Further analyses showed that no significant change in their behavior over the course of the sessions could be observed. Findings are discussed with regard to the caregiver's role during children's interactions with social robots and the implications for future interaction design.
Keywords: Education

Progressive Reduction of Iconic Gestures Contributes to School-Aged Children’s Increased Word Production - Rohlfing, Katharina; Mertens, Ulrich (Frontiers in Psychology)

Do Shy Preschoolers Interact Differently When Learning Language With a Social Robot? An Analysis of Interactional Behavior and Word Learning - Tolksdorf, Nils Frederik; Viertel, Franziska E.; Rohlfing, Katharina J. (Frontiers in Robotics and AI)
Temperamental traits can decisively influence how children enter into social interaction with their environment. Yet, in the field of child–robot interaction, little is known about how individual differences such as shyness impact on how children interact with social robots in educational settings. The present study systematically assessed the temperament of 28 preschool children aged 4–5 years in order to investigate the role of shyness within a dyadic child–robot interaction. Over the course of four consecutive sessions, we observed how shy compared to nonshy children interacted with a social robot during a word-learning educational setting and how shyness influenced children’s learning outcomes. Overall, results suggested that shy children not only interacted differently with a robot compared to nonshy children, but also changed their behavior over the course of the sessions. Critically, shy children interacted less expressively with the robot in general. With regard to children’s language learning outcomes, shy children scored lower on an initial posttest, but were able to close this gap on a later test, resulting in all children retrieving the learned words on a similar level. When intertest learning gain was considered, regression analyses even confirmed a positive predictive role of shyness on language learning gains. Findings are discussed with regard to the role of shyness in educational settings with social robots and the implications for future interaction design.

Wurzel - Heidgen, Michael (Metzler Lexikon literarischer Symbole)

This is my Fight Song - Uppenkamp, Vera; Neumann, Anna; Kammeyer, Katharina (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

"Wenn sich die Mitte auflöst...", ist das kein Verlust für die Religionspädagogik - ein bilanzierender Tagungsrückblick mit Augenzwinkern - Uppenkamp, Vera; Höger, Christian (Theo-Web. Zeitschrift für Religionspädagogik)

Art. Mädchen/Frauen - Uppenkamp, Vera (Das wissenschaftlich-religionspädagogische Lexikon im Internet www.wirelex.de)

"Gib mir was zu trinken, ich habe Durst..." Laientheologie nach Harald Schroeter-Wittke bei den Toten Hosen - Pinsch, Jan Christian (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Rezension zu Oliver Arnold, „Entjudung“ von Theologie und Kirche. Das Eisenacher „Institut zur Erforschung und Beseitigung des jüdischen Einflusses“ auf das deutsche kirchliche Leben 1939-1945, Bd. 6 Christentum und Zeitgeschichte, Leipzig 2020 - Pinsch, Jan Christian; Lerke, Stephanie (Paderborner Historische Mitteilungen)

Viel Lärm um die Stille. Die Geschichte des Raums der Stille an der Universität Paderborn im Spannungsfeld zwischen Religionsfreiheit und weltanschaulicher Neutralität - Pinsch, Jan Christian (Paderborner Historische Mitteilungen)

'Keine Gefangenen' oder 'Hyper Hyper' - Kommunikationen, Medien und Kulturen als Motoren gesellschaftlicher Transformationen. - Jacke, Christoph (Medienkultur als kritische Gesellschaftsanalyse. Festschrift für Rainer Winter.)

‚Deutsche’ Pop-Rezeption – zwischen journalistischen Trivialitäten und nationalen Eigenarten? - Jacke, Christoph (Gehört „deutsche“ Popmusik ins Museum? Materialien zu und von der Fünften Pop-Dekadentagung)

Ethische Bildung und inklusionsorientierter Religionsunterricht - Kammeyer, Katharina (Handbuch ethische Bildung. Religionspädagogische Fokussierungen)

This is my Fight Song - Kammeyer, Katharina; Neumann, Anna; Uppenkamp, Vera (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Improved non-linear devices for quantum applications - Gil López, Jano; Santandrea, Matteo; Roland, Ganaël; Brecht, Benjamin; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Silberhorn, Christine (New Journal of Physics)

Universal compressive tomography in the time-frequency domain - Gil López, Jano; Teo, Yong Siah; De, Syamsundar; Brecht, Benjamin; Jeong, Hyunseok; Silberhorn, Christine; Sánchez-Soto, Luis L. (Optica)

Musik und Sprache in Schauspielmusiken des 19. Jahrhunderts - Tumat, Antje

Learning to play golf for elderly people with subjective memory complaints: feasibility of a single‐blinded randomized pilot trial - Stroehlein, Julia K.; Vieluf, Solveig; Zimmer, Philipp; Schenk, Alexander; Oberste, Max; Gölz, Christian Johannes; van den Bongard, Franziska; Reinsberger, Claus (BMC Neurology)
Abstract Background Subjective Memory Complaints (SMC) in elderly people due to preclinical Alzheimer’s Disease may be associated with dysregulation of the Kynurenine Pathway (KP), with an increase in neurotoxic metabolites that affect cognition. Golf is a challenging sport with high demands on motor, sensory, and cognitive abilities, which might bear the potential to attenuate the pathological changes of preclinical AD. This trial investigated the feasibility of learning to play golf for elderly with cognitive problems and its effects on cognitive functions and the KP. Methods In a 22-week single-blinded randomized controlled trial, elderly people with SMC were allocated to the golf ( n = 25, 180 min training/week) or control group ( n = 21). Primary outcomes were feasibility (golf exam, adherence, adverse events) and general cognitive function (Alzheimer’s Disease Assessment Scale). Secondary outcomes include specific cognitive functions (Response Inhibition, Corsi Block Tapping Test, Trail Making Test), KP metabolites and physical performance (6-Minute-Walk-Test). Baseline-adjusted Analysis-of-Covariance was conducted for each outcome. Results 42 participants were analyzed. All participants that underwent the golf exam after the intervention passed it (20/23). Attendance rate of the golf intervention was 75 %. No adverse events or drop-outs related to the intervention occurred. A significant time*group interaction ( p = 0.012, F = 7.050, Cohen’s d = 0.89) was found for correct responses on the Response Inhibition task, but not for ADAS-Cog. Moreover, a significant time*group interaction for Quinolinic acid to Tryptophan ratios ( p = 0.022, F = 5.769, Cohen’s d = 0.84) in favor of the golf group was observed. An uncorrected negative correlation between attendance rate and delta Quinolinic acid to Kynurenic acid ratios in the golf group ( p = 0.039, r =-0.443) was found as well. Conclusions The findings indicate that learning golf is feasible and safe for elderly people with cognitive problems. Preliminary results suggest positive effects on attention and the KP. To explore the whole potential of golfing and its effect on cognitive decline, a larger cohort should be studied over a longer period with higher cardiovascular demands. Trial registration The trial was retrospectively registered (2nd July 2018) at the German Clinical Trials Register ( DRKS00014921 ).
Keywords: Clinical Neurology; General Medicine

Generalized tonic-clonic seizures are accompanied by changes of interrelations within the autonomic nervous system. - Vieluf, S; Hasija, Tanuj; Schreier, PJ; El Atrache, R; Hammond, S; Mohammadpour Touserkani, F; Sarkis, RA; Loddenkemper, T; Reinsberger, Claus (Epilepsy Behav)

Electrophysiological signatures of dedifferentiation differ between fit and less fit older adults - Gölz, Christian Johannes; Mora, Karin; Stroehlein, Julia Kristin; Haase, Franziska Katharina; Dellnitz, Michael; Reinsberger, Claus; Vieluf, Solveig (Cognitive Neurodynamics)
Abstract Cardiorespiratory fitness was found to influence age-related changes of resting state brain network organization. However, the influence on dedifferentiated involvement of wider and more unspecialized brain regions during task completion is barely understood. We analyzed EEG data recorded during rest and different tasks (sensory, motor, cognitive) with dynamic mode decomposition, which accounts for topological characteristics as well as temporal dynamics of brain networks. As a main feature the dominant spatio-temporal EEG pattern was extracted in multiple frequency bands per participant. To deduce a pattern’s stability, we calculated its proportion of total variance among all activation patterns over time for each task. By comparing fit (N = 15) and less fit older adults (N = 16) characterized by their performance on a 6-min walking test, we found signs of a lower task specificity of the obtained network features for the less fit compared to the fit group. This was indicated by fewer significant differences between tasks in the theta and high beta frequency band in the less fit group. Repeated measures ANOVA revealed that a significantly lower proportion of total variance can be explained by the main pattern in high beta frequency range for the less fit compared to the fit group [F(1,29) = 12.572, p = .001, partial η 2 = .300]. Our results indicate that the dedifferentiation in task-related brain activation is lower in fit compared to less fit older adults. Thus, our study supports the idea that cardiorespiratory fitness influences task-related brain network organization in different task domains.
Keywords: Cognitive Neuroscience

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Gölz, Christian Johannes; Mora, K.; Rudisch, J.; Gaidai, Roman; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Thermostable water reservoirs in the interlayer space of a sodium hectorite clay through the intercalation of γ-aminopropyl(dimethyl)ethoxysilane in toluene - Keil, Waldemar; Zhao, Kai; Oswald, Arthur; Bremser, Wolfgang; Schmidt, Claudia; Hintze-Bruening, Horst (Physical Chemistry Chemical Physics)
Thermostable compartmentalized sodium-water sites through intercalated γ-aminopropyl-dimethyl-ethoxy silane in synthetic hectorite.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Mechanism and equilibrium thermodynamics of H- and J-aggregate formation from pseudo isocyanine chloride in water - Hämisch, Benjamin; Huber, Klaus (Soft Matter)
Pseudo isocyanine chloride monomers equilibrate with H-oligomers and, separated by a threshold, with H-oligomers and fiber-like J-aggregates. The mechanism and thermodynamics of J-aggregate formation is interpreted with the concept of chain growth.
Keywords: Condensed Matter Physics; General Chemistry

Self-Assembled Fibrinogen Hydro- and Aerogels with Fibrin-like 3D Structures - Hense, Dominik; Büngeler, Anne; Kollmann, Fabian; Hanke, Marcel; Orive, Alejandro; Keller, Adrian; Grundmeier, Guido; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)
Keywords: Materials Chemistry; Polymers and Plastics; Biomaterials; Bioengineering

Multiresponsive Polymer Nanoparticles Based on Disulfide Bonds - Wagner, Maximilian; Krieger, Anja; Minameyer, Martin; Hämisch, Benjamin; Huber, Klaus; Drewello, Thomas; Gröhn, Franziska (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Thermodynamic Analysis of the Self‐Assembly of Pseudo Isocyanine Chloride in the Presence of Crowding Agents - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus (ChemSystemsChem)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Goelz, C.; Mora, K.; Rudisch, J.; Gaidai, R.; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Twenty-four-hour patterns in electrodermal activity recordings of patients with and without epileptic seizures. - Vieluf, S; Amengual-Gual, M; Zhang, B; El Atrache, R; Ufongene, C; Jackson, MC; Branch, S; Reinsberger, Claus; Loddenkemper, T (Epilepsia)

Exercise and sports after COVID-19-Guidance from a clinical perspective. - Halle, M; Bloch, W; Niess, AM; Predel, HG; Reinsberger, Claus; Scharhag, J; Steinacker, J; Wolfarth, B; Scherr, J; Niebauer, J (Transl Sports Med)

The effects of repetitive head impacts on postural control: A systematic review. - Bonke, EM; Southard, J; Buckley, TA; Reinsberger, Claus; Koerte, IK; Howell, DR (J Sci Med Sport)